Islam Profetik : Misi Profetik Pesantren Sebagai Sumber Daya Ummat - Suharto, Babun (TADRIS: Jurnal Pendidikan Islam, 2019)
Abstract This study is a study of the literature that emphasizes the concept of Prophetic Islam: Islamic Prophetic Missions as Community Resources, in this paper there are three important questions: How is the concept of prophetic Islam?; how is the concept of pesantren?; and how is the concept of prophetic in the Ummah edification? By using the content analysis concept to identify the three questions, the results of this study are the concept of prophetic mission as a community resource, and the prophetic concept in the development of the Islamic ummah. Â  Keyword: prophetic, pesantren, ummah